2018
DOI: 10.1039/c8ra00732b
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue endurance enhancement of Sn-doped Pb(Lu1/2Nb1/2)O3–PbTiO3 ceramics

Abstract: Fatigue endurance has been enhanced of Sn-doped Pb(Lu1/2Nb1/2)O3–PbTiO3 ceramics, exhibiting an abnormal self-rejuvenation of remnant polarization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The peaks of O–II are attributed to the formation of oxygen vacancies, and peak O–III resulted from the chemisorbed oxygen or dissociated oxygen . The intensity of peaks O–II is significantly smaller than that of O–I, which indicates that the content of oxygen vacancies in this ferroelectric material with perovskite structure is less and suppresses the generation of defective dipole pairs, and most of the oxygen ions are present in the lattice positions of the material, stabilizing the phase structure Figure d shows two valence states with different binding energies for the Ni 2p orbital.…”
Section: Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The peaks of O–II are attributed to the formation of oxygen vacancies, and peak O–III resulted from the chemisorbed oxygen or dissociated oxygen . The intensity of peaks O–II is significantly smaller than that of O–I, which indicates that the content of oxygen vacancies in this ferroelectric material with perovskite structure is less and suppresses the generation of defective dipole pairs, and most of the oxygen ions are present in the lattice positions of the material, stabilizing the phase structure Figure d shows two valence states with different binding energies for the Ni 2p orbital.…”
Section: Results and Discussionmentioning
confidence: 94%
“…47 The intensity of peaks O−II is significantly smaller than that of O−I, which indicates that the content of oxygen vacancies in this ferroelectric material with perovskite structure is less and suppresses the generation of defective dipole pairs, and most of the oxygen ions are present in the lattice positions of the material, stabilizing the phase structure. 48 NiO and Sb 2 O 3 were overdosed. The microstructure, domain morphology, dielectric and electrical properties, ferroelectric analysis, and valence changes of Sb elements were systematically investigated for PNN−PSN−PMN−PZT ceramics and the overdose group.…”
Section: Xps Measurementmentioning
confidence: 99%
“…Table 2 lists the average of remanent polarization, coercive field, and current at 1, 10 5 , and 10 7 cycles. Ferroelectric properties degradation has been associated with intrinsic defects, redistributions of imperfection after switching the dipole process, and punctual defects by doping [ 40 ]. Therefore, BCTZ8-5 showed a high electrical fatigue resistance, which makes it a promising candidate for actuator or nonvolatile random-access memory applications when prepared in thin film form [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The content of Sn indirectly reflects the content of defect dipoles. 19,20 Electrical properties were measured using standard ferroelectric system (TF2000 Analyzer, aix-ACCT System GmbH). Capacitance-voltage (C-V) curves were measured by superimposing a small-signal fast-varying (1 kHz) AC electric field (E AC ) on a slow-varying (0.1 Hz) AC electric field.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous works revealed that defect dipoles formed as false(SnTiVO··false)× in this material system due to the change in valence of Sn. The content of Sn indirectly reflects the content of defect dipoles 19,20 . Electrical properties were measured using standard ferroelectric system (TF2000 Analyzer, aixACCT System GmbH).…”
Section: Methodsmentioning
confidence: 99%